Minutes of the Thirteenth Semi-Annual Meeting of the Rocky Mountain Coal Mining Institute, Held at Rock Springs, Wyo., and Salt Lake City, Utah, June 28, 29 and 30, 1921 (Rocky Mountain Coal Mining Institute, 1921)
On Monday, June 27, 1921, at 6 p. m., twenty-four members of the Institute from. Colorado and New Mexico, left Denver on the Union Pacific for Rock Springs, Wyoming, arriving there at 9:42 a. m., June 28th. The party was met at the depot by the Rock Springs committee and a large number of the local Institute members. The day was spent in visiting the Central Power Plant of, the Union Pacific Coal Company and adjacent mine, the new 'E Plane, the Reliance, Dines, Winton and Sweetwater coal properties in the district. At noon a very elaborate lunch was served in the First Aid Building at the Reliance mine, which was most heartily enjoyed by all. In the evening the members and friends visited the new Rialto theater and saw the pictorial exposition of the' "Sky Pilot". The evening terminated with a dance in the ballroom of the Masonic Temple from 9:30 until midnight, concluding one of the most enjoyable days which the Institute has ever spent in Rock Springs. At 12:3o a. m. the original party, augmented by six members from Rock Springs, were again enroute to Salt Lake City, arriving there at 8:30 in the morning of Wednesday, June 29th. The Hotel Utah had been selected by the local, committee as the headquarters for the convention, and the majority of the -members at once proceeded to that place where the books were opened and the paying of dues and registration of the members were carried on until 11:45 a.m. At noon a majority of the members were entertained at the L. D. S. Tabernacle with an organ recital, which was up to its usual standard of excellence.